AKTUALISASI PERAN IBU SEBAGAI MADRASAH PERTAMA DAN UTAMA BAGI ANAK DI ERA 4.0 - Parhan, Muhamad (JMIE (Journal of Madrasah Ibtidaiyah Education), 2020)
The figure of a mother has an important role for the growth and development of children. Mothers as first and foremost madrasa who always accompany children certainly have to understand the factual conditions in the current era. As we know in the 4.0 era, the progress of digital technology is growing rapidly. The progress of digital technology is of course very influential in various aspects of human life. It is undeniable that the progress of digital technology also affects children's development. Therefore we aim to further examine the actualization of the role of mothers as first and foremost madrassas for children in the 4.0 era. The approach the researcher uses is qualitative-quantitative (mix method). The research instrument by distributing questionnaire questionnaires as primary data to respondents in the city of Bandung and surrounding areas aims that we want to look deeper into the awareness of the role of mothers in the 4.0 era. Data processing by triangulation with relevant theories. So that the final results of researchers get answers from mothers in the city of Bandung and surrounding areas actually already know the impact of the industrial revolution 4.0 era for children. The mothers agreed to the direction and control that was carried out to the children that started from the realm of the family. So the mother as the first madrasa for children is needed.Â